Age determination in crossbred calves using different techniques - JAIN, M K; SINGH, N P; DAVE, B K (The Indian Journal of Animal Sciences, 2014)
The present investigation was carried out on GO recently born crossbred calves up to 90 days of age to evaluate different methods of age determination, viz. visual Observation of rostral teeth, teeth measurement and muzzle prints. The eruption of teeth from the gum line was faster during first and second fortnight. In the mapping method, the tooth area representing its growth was significantly different between genetic groups i.e. A ( ½ Jersey ¼ Holstein Friesian and Gir). B (¼ Holstein Friesian ¼ Gir) and C (½ Brawn Swiss ¼ Holstein Friesian and ¼ Gir) , whereas, in the visual coding method, there was no significant difference in the growth of tceth between genetic groups. The mapping method used proved more efficient in determining the age. The different muzzle print characteristics namely ridged beads, clustered beads and converted beads indicated that number of beads was higher on the muzzle in the earlier age of calf. The association of age with various methods ofage determination in crossbred calves up to the age of 90 days was significant ( P< 0.01). Prediction equation indicated higher R2 values for teeth area (62.41 to 92.10) followed by visual code (57.76 to 85.04) and muzzle print (40.96 to 44.89). The reliability for predicting the age varies between genetic groups of crossbred as well as methods of age determination. The R2 values indicated that teeth mapping was more precise method than teeth eruption and muzzle print for age prediction.